GEOCHEMISTRY OF THE EMEISHAN FLOOD BASALTS AT YANGLIUPING, SICHUAN, SW CHINA: IMPLICATIONS FOR SULFIDE SEGREGATION - Song X.-Y.; Zhou M.-F.; Sun M.; Qi L.; Keays R.R.; Cao Z.-M. (My University, 2006)
A well-developed, 1,000 m thick basaltic sequence in the Yangliuping region, northern part of the Emeishan basalt province, includes the Lower and Middle Units of tholeiitic basalts and an Upper Unit of both tholeiites and subalkalic basalts. The basalts contain 42-55 wt% SiO2 and 4.1-8.3 wt% MgO. Most of these lavas have Gd/Yb > 2.0, Zr/Nb < 12, and εNd(260Ma) values from +2.5 to +4.7. The platinum-group elements (PGE) are very mildly depleted in most of the basalts which contain 8-19 ppb Pt and 7-27 ppb Pd. However, a significant proportion of the Middle Unit basalts are strongly depleted in PGE with some samples having concentrations lower than detection limits. They have extremely high Zr/Nb ratios (up to 14.5) and low εNd(260Ma) values (+3.21 to +0.65), features of extensive lower crustal contamination. Some samples in this unit have high Ni/Pd (3,965-61,198) and low Pd/Cr (410,000-3,930,000) ratios, indicating sulfide segregation and PGE depletion prior to eruption. The primary magmas were S-undersaturated and derived from partial melting at variable depths in the upper mantle. The early and late stage magmas, as represented by the Lower and Upper Units, underwent AFC processes which induced mild S-saturation and PGE depletion in some of the basalts, whereas the magmas represented by the Middle Unit experienced more extensive crustal contamination resulting in stronger S-saturation and in most cases significant PGE depletion. © Springer-Verlag 2006.